The ENVIRONMENTAL SERVICES COMMUNICATION STYLE IN CREATING ENVIRONMENTAL CLEAN AWARENESS BINJAI CITY COMMUNITY: GAYA KOMUNIKASI DINAS LINGKUNGAN HIDUP DALAM MENCIPTAKAN KESADARAN BERSIH LINGKUNGAN MASYARAKAT KOTA BINJAI - Adi Syahputra (Prodi Manajemen Dakwah STAIN Mandailing Natal, 2021)
The author conducted this study aimed to determine the communication style of the Department of the Environment, programs, and the obstacles in increasing awareness of the clean environment of the people of Binjai City. This type of research is descriptive using a qualitative approach. Research informants consisted of leaders and employees of the Department of the Environment by means of purposive sampling. Data collection tools are carried out through the stages of observation, interviews and documentation. The data analysis technique uses data reduction, data presentation and conclusion drawing. Based on the results of the study, it was found that the communication model of the Department of the Environment in increasing environmental awareness of the people of Binjai City was as follows: two-way communication style, motivational communication style, one command communication style and control communication style. The researcher also found that there are several programs from the Department of the Environment in increasing public awareness of environmental cleanliness in the City of Binjai, namely as follows: garbage bank, garbage collection, street cleaning, banner installation and mini garden construction. The researcher also found the obstacles faced by the Environment Agency, namely technical, semantic, and cultural barriers.